Design of Rectifying Circuit and Harmonic Suppression Antenna for RF Energy Harvesting - Ahmed, S.; Zakaria, Z.; Husain, M. N.; Alhegazi, A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this paper a rectifying circuit and antenna designs at frequency of 2.45 GHz are presented. The antenna has a form of two-layer through which high gain and harmonic rejection property are embedded. The rectifying circuit consists of two stages with four fast switching diodes to provide high output DC voltage. The power combiner is used to combine the two stages and maximize the output DC voltage. The equivalent circuits of both antenna and rectifying circuit that are derived from lumped components, are presented. From measurement, the proposed rectifying circuit can achieve 78.7 % with load resistance 4 KΩ and input power of 20 dBm. The advantages of the proposed rectifying antenna are that the harmonic rejection filter is not needed and the cost of the overall rectifying antenna design is low. These benefits make it suitable for RF energy harvesting applications.